Capacity Building, Principals’ job Performance and Teachers’ job performance in Public Secondary schools in Federal Capital Territory, Abuja, Nigeria - Gbaeprekmo, Oweikpodor Vera; Enwerim, Nwangwa Julian; Kayode, Olofinkua Vincent (MultiTech Publisher, 2024)
The study examined how capacity building affected the work performance of PBECD (Post-Basic Education and Career Development) principals and teachers in the Federal Capital Territory of Abuja, Nigeria. For this investigation, a descriptive survey research design was utilized. Principals and teachers at public Post-Basic Education and Career Development (PBECD) schools in the Federal Capital Territory (FCT) of Abuja, Nigeria, made up the study's population. 120 teachers and 36 principals make up the study's sample size. Purposive and random sampling strategies were employed in the research. For this study, a structured questionnaire was the tool used to collect data. At the University of Abuja, specialists from the Department of Educational Management verified the instruments. To ascertain the reliability coefficient, the test-retest approach was employed. In FCT, the study found a positive correlation between capacity building, the work performance of principals, and the work performance of teachers in PBECD. Building capacity supports PBECD teachers' job performance and facilitates efficient school administration. The study suggests that in order to support an efficient capacity building program for school principals and teachers in the PBECD program, the government should enhance funding for PBECD in the Federal Capital Territory.